Studi Kualitatif : Dampak Ledakan Populasi Hydrilla Verticilatta terhadap Adaptasi Pemancing di Situ Rancamaya - Sony Stiyadi; Zaky Agung Hugo; Danu Juliansyah; Muhammad Adib Amrullah (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the impact of the population explosion of the aquatic plant Hydrilla verticillata on community adaptation, particularly among anglers at Situ Rancamaya. The uncontrolled growth of Hydrilla verticillata has covered at least half of the water surface in Situ Rancamaya. This research employs a qualitative approach using observation and interview methods, involving a number of local anglers as respondents. The instruments used include research questions and interview guidelines, which were analyzed using Miles and Huberman's analytical technique. The findings indicate that anglers perceive both negative and positive impacts from this phenomenon. The variation in perceptions among respondents demonstrates that each angler has different experiences and observations in responding to the situation. This study highlights that ecological phenomena can have significant social implications.